2020
DOI: 10.3390/ijms21010360
|View full text |Cite
|
Sign up to set email alerts
|

Antrodan Alleviates High-Fat and High-Fructose Diet-Induced Fatty Liver Disease in C57BL/6 Mice Model via AMPK/Sirt1/SREBP-1c/PPARγ Pathway

Abstract: Non-alcoholic fatty liver disease (NAFLD) and -steatohepatitis (NASH) imply a state of excessive fat built-up in livers with/or without inflammation and have led to serious medical concerns in recent years. Antrodan (Ant), a purified β-glucan from A. cinnamomea has been shown to exhibit tremendous bioactivity, including hepatoprotective, antihyperlipidemic, antiliver cancer, and anti-inflammatory effects. Considering the already well-known alleviating bioactivity of A. cinnamomea for the alcoholic steatohepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 59 publications
3
79
1
1
Order By: Relevance
“…A previous study has indicated that AMPKα activation plays a key role in cholesterol homeostasis by inhibiting hepatic cholesterol synthesis [ 26 ]. AMPK activation can down-regulate lipogenic transcription factors PPARγ and SREBP-1c, thereby inhibiting the lipogenic genes [ 27 , 28 ]. Supplementation of high MW chitosan has been demonstrated to alleviate the lipogenesis in HF diet-fed rats through the mechanisms of AMPK activation and lipogenesis-associated gene inhibition [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has indicated that AMPKα activation plays a key role in cholesterol homeostasis by inhibiting hepatic cholesterol synthesis [ 26 ]. AMPK activation can down-regulate lipogenic transcription factors PPARγ and SREBP-1c, thereby inhibiting the lipogenic genes [ 27 , 28 ]. Supplementation of high MW chitosan has been demonstrated to alleviate the lipogenesis in HF diet-fed rats through the mechanisms of AMPK activation and lipogenesis-associated gene inhibition [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…3 C). 81 , 82 , 83 , 84 , 85 , 86 All the Chinese medicines in Fig. 3 C reduced blood glucose levels.…”
Section: Chinese Herbs and Fatty Liver Diseasementioning
confidence: 91%
“…The consumption of high fructose can cause insulin resistance (IR), excessive production of reactive oxygen species (ROS), hepatic steatosis, liver malfunction, and depletion of the hepatocyte population [ 17 , 18 ]. Oxidative stress, induced by a high-energy diet, builds up to the genesis and progression of steatohepatitis from steatosis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%